INDUKSI KALUS PADA TANAMAN ANGGREK VANDA TRICOLOR LINDL. VAR. SUAVIS, UPAYA PENYEDIAAN TARGET TRANSFORMASI MELALUI AGROBACTERIUM TUMEFACIENS - Dwiyani, Rindang (JURNAL AGROTROPIKA, 2013)
The aim of the current research was to find out a method in producing calli of Vanda tricolor orchid for target on Agrobacterium-mediated transformation.  Six to seven months (after sowing) of orchid seedlings were used as source of planting material.  Seedlings were sliced into small parts i.e. leaves, shoots and roots.  Roots were discharged, while leaves and shoots were used as explants. Explants then were planted on the Murashige and Skoog Medium added with 2ppm 2,4-D for calli induction.  Two kinds of sugar concentration i.e. 0% sucrose and 3% sucrose were used as treatment and each was added on those calli induction medium.  The results showed that the appropriate method for producing calli on V. tricolor orchid was using shoots as source of explants and planting them on Murashige and Skoog Medium added with 2ppm 2,4-D and with no sucrose.  Keywords: calli, V. tricolor orchid, shoots, leaves, sucrose